Disproportionate admixture improves reintroduction outcomes despite the use of low‐diversity source populations: population viability analysis for a translocation of the greater stick‐nest rat. (18th August 2022) - Onley, I. R.; White, L. C.; Moseby, K. E.; Copley, P.; Cowen, S.
Abstract: Translocation is becoming an increasingly important approach to threatened species conservation. Coupled with the knowledge that maximizing genetic diversity aids population establishment, the growing use of translocations can place unsustainable harvesting pressure on critical and vulnerable source populations. However, adaptive, genetically informed modelling tools such as Population Viability Analysis (PVA) can be used to predict translocation outcomes and optimize harvesting strategies. In this study, we use PVAs for the frequently translocated greater stick‐nest rat ( Leporillus conditor ) to demonstrate the value of admixing founder populations for translocation, even when one source population is deemed genetically depauperate. This approach not only maximizes genetic diversity in the translocated population but reduces harvesting pressure on critical populations. Further, we show that admixed harvesting ratios can be skewed significantly towards the genetically depauperate population in order to further protect the critical population while still producing favourable outcomes, providing adequate founder numbers are used. As many threatened species are limited to fragmented and bottlenecked populations, these results are broadly applicable to the science of reintroduction biology, and demonstrate the value of PVAs for preliminary translocation planning and species management. Abstract : A) Population size, B) expected heterozygosity, and C) comparison of inbreeding coefficients (mean and SD) of translocated greater stick‐nest rats under each simulated population viability analysis scenario over 50 years. Symbols denote the following; *single source, †multiple source, ‡low founder numbers, §baseline founder numbers, ¶high founder numbers, #skewed harvesting ratio. Our models show that skewed harvesting ratios towards genetically depauperate source populations can produce favourable outcomes following translocation, highlighting a promising approach to protect critical populations without jeopordizing reintroduction programs.